A study on local expression of NF-ÎºB, CCL2 and their involvement in intratumoral macrophage infiltration in breast cancer - Tewari, B N; Singh Baghel, K; Tripathi, C; Dubey, P; Bhatt, M L B; Kumar, V; Mati Goel, M; Singh Negi, M P; Misra, S (Cellular and Molecular Biology, 2016)
NF-ÎºB has been implicated in mechanisms promoting inflammation in tumor microenvironment leading to breast cancer metastasis. Owing to critical role of CCL2 during metastasis, particularly in its capacity to act as a chemoattractant for macrophages and their precursors i.e monocytes, we decided to explore if pro-metastatic function of NF-ÎºB could be attributable to CCL2 and/or macrophage infiltration. Through our study we provide experimental and clinical evidence in support of co-ordinated expression of chemokines CCL2, NF-ÎºB and intratumoral macrophage content particularly with respect to breast cancer, with an additional evidence of these three variables being key determinant for poor prognosis and diminished survival amongst breast cancer patients both independently as well in a coordinated manner. The mean fold increase in mRNA expression level of NF-ÎºB and CCL2 indicated that it was over expressed 13.57 and 13.18 fold respectively in tumor tissue as compared to adjacent normal tissue. Among these Immunohistochemistry expression of CD68 marker showed that 62 patients (66.7%) had low/moderate CD68 expression while 31 patients (33.3%) had strong expression. All three variables viz.NF-ÎºB, CCL2 and CD68 showed significant (p<0.05 or p<0.01 or p<0.001) respectively associations with both clinicopathological (except CD68 with stage) and hormone receptors (ER, PR and Her2/neu) and their co-expressions indicating these as predictors of breast cancer. In this study we decipher the possible molecular mechanism by way of which NF-ÎºB may promote breast cancer metastasis. Our study has clinical relevance as it establishes significance of these three variables as potential predictive markers to be employed in breast cancer.